Tripusat Pendidikan: Mutu Pendidikan - Saifullah, Saifullah; Ilyas, Mukhlisuddin; Putra, Mulia (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to determine the role of educational tricenter institutions in efforts to improve the quality of education in Indonesia. This research is qualitative research. The research used is descriptive qualitative research. Descriptive qualitative research is in the form of research with a case study method or approach. This research focuses intensively on one object that studies it as a case. Triangulation in credibility testing is defined as checking data from various sources in various ways and at various times. Data collected with interview techniques in the morning when the source person is still fresh, not many problems will provide more valid data so that it is more credible. Testing the validity of data can be done by checking with interviews, observations, or other techniques in different times/situations. The results of interviews with several school principals with the discussion of the education tricenter that support once in the program, support the implementation of the independent curriculum as a concrete step whose implementation in elementary schools, it can be seen in improving the quality of education from year to year. The implementation of P5 can be seen from the support of parents. So that what we hope is achieved according to the mission of the school